THE EFFECT OF THERAPEUTIC EXERCISES IN REDUCING PAIN, DORSAL CONVEXITY AND ELASTICITY OF THE SPINE MUSCLES OF WOMEN WITH OSTEOPOROSIS - Kadum Al-Attabi, Dr. Sameerah Abdulrassol; Abdul-hammed Al-Rubaie, Prof. Dr. Suhad H. (International Journal of Psychosocial Rehabilitation, 2019)
The research problem lies in that most women in the age of 40 suffer from osteoporosis, which results in many complications, which prompted the researcher to study this problem and reduce the severity of the symptoms resulting from it. Reducing dorsal pain and humping and increasing flexibility of muscles working on spinal movement. As for the research hypotheses, they were: The presence of statistically significant differences in the degree of pain and dorsal hunchback between the pre and post-tests of the research sample and in favor of the post test. As well as the existence of statistically significant differences between the pre and post-tests in the flexibility of the spinal muscles of the research sample. The researcher used the experimental method and the main sample of the experiment consisted of 13 women with osteoporosis, aged between (45-55). The experiment was conducted, and then the results were statistically treated in order to clarify the differences between the pre and post-tests. The researcher concluded several conclusions, including: Therapeutic exercises have a positive effect on the eye. The researcher also recommended several recommendations, including: the use of therapeutic exercises prepared by the researcher in particular and physical activity in general in reducing the symptoms associated with osteoporosis.